Do Intangible Assets Drive Profitability? An Empirical Analysis of Nepalese Commercial Banks - Adhikari, Tek Bahadur; Sapkota, Liladhar (AMC Journal (Dhangadhi), 2026)
Intangible assets such as software, goodwill, trademarks, human capital, intellectual assets and copyrights are increasingly recognized as critical drivers of competitive advantage and profitability in modern business organizations. This study investigates the impact of investment in intangible assets on the profitability of Nepalese commercial banks. Employing an ex post facto research design, the analysis is based on panel data from 19 commercial banks over eight years (from 2074/75 to 2080/81), corresponding to 2017/18 to 2023/24, yielding 152 observations. A Quantile regression model is used to assess the relationship and impact, with net profit after tax (NPAT) as the dependent variable, investment in intangible assets as the independent variable, and bank size as a control variable. Additionally, bank age and ownership type are incorporated as moderating variables. The results reveal that investment in intangible assets has a positive and statistically significant impact on profitability (NPAT) at the 50th percentile and above. Furthermore, age and size of the banks also positively influence NPAT, while ownership type does not exhibit a significant effect on NPAT. These findings highlight the significance of investing capital in intangible assets for strategic importance. Banks’ period of experience (age) also proves earning capacity with their physical and intellectual resources. Banks’ policymakers can rethink the investment size and nature of intangible assets to contribute to bank profitability. The study has not categorized the intangible assets into individual components. Each component of intangible assets may contribute in profitability individually, which has not been covered in this.